2022
DOI: 10.3390/molecules27072208
|View full text |Cite
|
Sign up to set email alerts
|

LC/ESI/TOF-MS Characterization, Anxiolytic and Antidepressant-like Effects of Mitragyna speciosa Korth Extract in Diabetic Rats

Abstract: In this study, the attenuative effects of the hydro-alcoholic extract from Mitragyna speciosa (MSE) against diabetes-induced anxiety and depression-like behaviors were examined. In addition, UPLC/ESI/TOF-MS analysis was performed to identify the phytochemical nature of MSE. DM was induced using a combination of high fructose/streptozotocin, and the diabetic rats were treated with MSE (50 and 200 mg/kg) for 5 weeks. After treatment, the animals were subjected to a forced swim test, open field test and elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Diabetes causes increased hippocampal levels of proinflammatory cytokines, such as TNF-α, NF-ĸB and IL-6, decreased neurotrophic factors, such as BDNF, NGF and IGF-1, 19 increased hippocampal lipid peroxidation and plasma glycated hemoglobin levels, and decreased antioxidant status as assessed by GSH, 20 and decreased insulin receptor phosphorylation in rat hippocampus, decreased ATP and glucose transporter 4 (GLUT4) expression, 21 decreased levels of glutamate, serotonin and dopamine in the hippocampus and associated hippocampal neuron apoptosis, 22 impaired regulation of hippocampal oxidative enzymes (GSH, SOD, CAT, LOOH), 23 increased brain proinflammatory cytokines (TNF-α, IL-6 and IL-1β) and MDA levels, and reduced SOD; CAT and GSH activity. 24 One of the important neurotransmitters in the pathophysiology of diabetic depression is ACh, and patients suffering from depression have high brain ACh levels and remain at this level as long as depression persists. 7 Donepezil is a synthetic AChE inhibitor that enhances cholinergic function by increasing the amount of ACh in the central nervous system and thus its interaction with the relevant receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes causes increased hippocampal levels of proinflammatory cytokines, such as TNF-α, NF-ĸB and IL-6, decreased neurotrophic factors, such as BDNF, NGF and IGF-1, 19 increased hippocampal lipid peroxidation and plasma glycated hemoglobin levels, and decreased antioxidant status as assessed by GSH, 20 and decreased insulin receptor phosphorylation in rat hippocampus, decreased ATP and glucose transporter 4 (GLUT4) expression, 21 decreased levels of glutamate, serotonin and dopamine in the hippocampus and associated hippocampal neuron apoptosis, 22 impaired regulation of hippocampal oxidative enzymes (GSH, SOD, CAT, LOOH), 23 increased brain proinflammatory cytokines (TNF-α, IL-6 and IL-1β) and MDA levels, and reduced SOD; CAT and GSH activity. 24 One of the important neurotransmitters in the pathophysiology of diabetic depression is ACh, and patients suffering from depression have high brain ACh levels and remain at this level as long as depression persists. 7 Donepezil is a synthetic AChE inhibitor that enhances cholinergic function by increasing the amount of ACh in the central nervous system and thus its interaction with the relevant receptors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ]. Increasing evidence indicates that kratom extract could be used to treat metabolic syndrome, i.e., controlling blood glucose and lipid profiles [ 30 , 31 , 32 , 33 , 34 , 35 ], even though information about the underlying molecular mechanisms or targeted molecules, in which bioactive compounds in kratom leaves exhibit these actions, is limited. There has been only one previous study that reported the potential of kratom leaf extracts in glucose-lowering effects, in which the methanolic extract of kratom leaves and the major constituent mitragynine promoted in vitro glucose uptake to muscle cells via glucose transporter-1 (GLUT-1) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, through in vitro and in vivo studies, kratom has been observed to exhibit various pharmacological properties, such as antioxidant, anti-inflammation, antibacterial, antiproliferative, and anti-analgesic properties [ 28 , 29 ]. Although previous studies have reported that kratom leaves exhibit activities that control diabetes and lipid profile [ 30 , 31 , 32 , 33 , 34 , 35 ], there is still a lack of scientific evidence related to the inhibitory effects and mechanism of enzymatic activities. Thus, in this research, we aimed to evaluate the α-glucosidase and pancreatic lipase inhibitory activities of kratom leaves.…”
Section: Introductionmentioning
confidence: 99%
“…The enzymes superoxide dismutase (SOD) and catalase (CAT) are also important antioxidant enzymes that serve to prevent the toxicity of hydrogen peroxide (H 2 O 2 ). They were observed to be markedly increased in the brain tissue with the treatment of kratom hydroalcoholic extract in an animal model [147]. It has been discovered that elevated amounts of Aβ oligomers promote the development of oxidative stress, neuroinflammation, synapse loss, and nerve cell death.…”
Section: Neurological Effects By Gene Regulationmentioning
confidence: 99%